An Exploratory Examination of Burnout in NCAA Division II Athletes - Judge, Lawrence W.; Bell, Robert J.; Theodore, Rachel; Simon, Laura; Bellar, David (Journal of Intercollegiate Sport, 2012)
The purpose of this study was to assess the causes of burnout among student-athletes in Division II institutions. The authors distributed the Athlete Burnout Questionnaire (ABQ) to 125 undergraduate student-athletes enrolled at three Division II colleges and universities. The athletes competed in various sports. A 2 (Gender) × 2 (Type of Scholarship) × 2 (School Status) analysis of variance revealed that women and men reported different levels of burnout dependent upon type of scholarship. Men with no scholarship reported the lowest levels of burnout among the three types (None/Academic/Athletic), whereas women with no type of scholarship reported the highest levels of burnout. The authors discuss the results and offer implications, limitations, and future directions.